2010
DOI: 10.3945/jn.109.120188
|View full text |Cite
|
Sign up to set email alerts
|

Eating Competence of Elderly Spanish Adults Is Associated with a Healthy Diet and a Favorable Cardiovascular Disease Risk Profile

Abstract: Eating competence (EC), a bio-psychosocial model for intrapersonal approaches to eating and food-related behaviors, is associated with less weight dissatisfaction, lower BMI, and increased HDL-cholesterol in small U.S. studies, but its relationship to nutrient quality and overall cardiovascular risk have not been examined. Prevención con Dieta Mediterránea (PREDIMED) is a 5-y controlled clinical trial evaluating Mediterranean diet efficacy on the primary prevention of cardiovascular diseases (CVD) in Spain. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
36
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 22 publications
7
36
1
Order By: Relevance
“…The mean eating competence score of Hispanics in the 2007 validation study (15) was 32.2 6 8.9, which is similar to the mean ecSI/LI score of 33.2 6 8.6 for the 240 Hispanic parents in this sample. However, the mean ecSI/LI score of the 31 Hispanics in the 2011 validation study (16) was only 28.2 6 12.4 and the eating competence score of elderly Spaniards (measured with a survey translated specifically for Spaniards) was 30.9 6 6.3 (12), suggesting further study of Hispanic eating competence is warranted. Indeed, the potential of Hispanic ethnicity to moderate parent eating and food-related behaviors appears not to be a constant but rather a function of acculturation, country of origin, and income (33,34).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The mean eating competence score of Hispanics in the 2007 validation study (15) was 32.2 6 8.9, which is similar to the mean ecSI/LI score of 33.2 6 8.6 for the 240 Hispanic parents in this sample. However, the mean ecSI/LI score of the 31 Hispanics in the 2011 validation study (16) was only 28.2 6 12.4 and the eating competence score of elderly Spaniards (measured with a survey translated specifically for Spaniards) was 30.9 6 6.3 (12), suggesting further study of Hispanic eating competence is warranted. Indeed, the potential of Hispanic ethnicity to moderate parent eating and food-related behaviors appears not to be a constant but rather a function of acculturation, country of origin, and income (33,34).…”
Section: Discussionmentioning
confidence: 95%
“…ecSatter emphasizes eating enjoyment, internal regulation of intake and letting body weight be dictated by lifestyle and genetics, using skills to provide meals regularly, and eating a variety of foods for pleasure rather than just to meet dietary guidelines (12). Although ecSatter does not target food groups, portion sizes, nutrient intake, or a desired weight, studies with samples varied in age, gender, and economic status have shown that competent eaters have a higher diet quality (12,13); fewer risks for cardiovascular disease, including lower blood pressure, lower LDL-cholesterol, and increased HDL-cholesterol (11,14); lower BMI, greater weight satisfaction; more self-reported physical activity; better developed food resource management skills (15)(16)(17); higher sleep quality (18) and fewer correlates of disordered eating, e.g., emotional eating and drive for thinness (15,16). In addition, parent eating competence spans from high to very low, suggesting opportunity to detect a moderating influence (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…2 Uses a written spending plan or budget for food, About Eating (P ¼ .07). 3 Keeps track of food-related purchases or expenses, About Eating (P ¼ .02). All differences between food-secure and food-insecure Click 'n Go participants were not significant.…”
Section: Discussionmentioning
confidence: 99%
“…1 Eating competence is associated with greater dietary quality, 2,3 reduced cardiovascular risk, 3,4 increased physical activity, 5 fewer symptoms of disordered eating, including weight satisfaction and normal body mass index, [6][7][8][9] better sleep quality, 10 and parent modeling healthful eating behaviors. 11 Satter offered descriptions of ecSatter-driven nutrition education and guidance for adoption, 12 and nutrition education programs congruent with ecSatter have been suggested.…”
Section: Introductionmentioning
confidence: 97%
“…Up to now the PREDIMED study has demonstrated that adherence to the MD is associated with a reduced incidence of diabetes [5][6], the metabolic syndrome [7], hypertension [8], and better control of other cardiovascular risk factors [9][10]. In fact, Estruch et al [11] have recently reported that a MD intervention reduces the incidence of cardiovascular events by 30% in subjects at high cardiovascular risk.…”
Section: Introductionmentioning
confidence: 99%